Identification and management of toxigenic fusarium species associated with fusarium head blight and fusarium crown rot of wheat in South Africa - Van Coller, Gerhardus Johannes (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhDAgric)--Stellenbosch University, 2018.